Correlation detection as a general mechanism for multisensory integration - Cesare V. Parise (Nature Portfolio, 2016)
The human brain integrates inputs across multiple sensory streams into a unified percept. Here Parise and Ernst present a model that assesses the correlation, lag and synchrony of multisensory stimuli, and predicts psychophysical performance on multisensory temporal and spatial tasks.